Rekonstruksi Konsep "Tanah Terlantar" dalam UUPA : Implikasi Terhadap Pengelolaan HGU yang Tidak Produktif - Desinta Desinta; Parlaungan Gabriel Siahaan; Brent Hizkia Padang; Dinda Amalia Nasution; Rachel Meilisa Pakpahan; Putri Yohanna Damanik (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The concept of ‘abandoned land’ in the Basic Agrarian Law (UUPA) No. 5 of 1960 faces interpretation challenges that impact the effectiveness of the management of unproductive Cultivation Rights (HGU). This research aims to analyse the reconstruction of the concept of abandoned land in UUPA and its implications for the management of unproductive HGU to support the optimisation of agricultural land use. This research is conducted through normative juridical with qualitative descriptive analysis of laws and regulations, court decisions, and related literature. The research findings show that the concept of abandoned land in the UUPA is still multi-interpretive, especially regarding the criteria of ‘not being cultivated according to the circumstances or nature and purpose of the right’. This has led to inconsistencies in the application of sanctions against HGU holders who leave their land unproductive. Concept reconstruction is needed by clarifying the objective parameters of productivity, the period of neglect, and law enforcement mechanisms. The implications of this research indicate the need for regulatory revisions to strengthen legal certainty in HGU management, as well as the development of more effective policy instruments to prevent abandonment of agricultural land to support national food security and social justice in agrarian reform.